Independence Day celebration in growing the spirit of nationalism in Sukahurip Village - Gunawan, Nur Ani; Putri, Indri Dwinda (Universitas Pendidikan Indonesia, 2024)
Commemoration of the Independence Day of the Republic of Indonesia is one of the programs held by UPI KKNT students in Sukahurip Village. This service documents and analyzes competition activities commemorating the 78th Indonesian Independence Day in Sukahurip Village. Activities involve competitions such as carnivals, dongdang, and gate decorating, aiming to foster a feeling of love for the country, remembering the nation's struggle's history, and appreciating Indonesian culture's noble values and diversity. The competition activity created a moment of togetherness and patriotism in Sukahurip Village. Through the creativity and innovation displayed in each competition, people are inspired to get involved in the development of their region. Social solidarity is strengthened primarily through active participation in the preparation and implementation of dongdang competitions. Suggestions for further programs could include integration of vertical and horizontal approaches, active community participation in planning, long-term impact evaluation, analysis of community welfare, comparative studies with similar villages, development of local development models, and further studies on the role of KKN students. Hopefully, this service program can contribute to understanding the impact of competition activities in Sukahurip Village.